The Impact of Social Media Factors on Consumers Engagement: An Empirical Study in Malaysia - Ting Wei PHONG; Ajitha ANGUSAMY; Jayanty KUPPUSAMY; Kavitha RAMAN (Communications of International Proceedings, 2024)
The use of social media has transformed the way companies engage with consumers. It gives companies extra potential to attract and retain customers while also enabling them to educate, inspire, and hold onto their target market. Businesses may cultivate consumer loyalty through making social media consumer engagement of the utmost importance. The study aims to investigate the impact of social media factors namely content quality, customer contact quality, brand page interactivity, and brand post novelty  in boosting consumer engagement. The respondents are Malaysians aged 18 to 40 years old. The convenience sampling method is used for data collection and a sample of 250 responses was obtained. The data collected was analysed using SPSS and Smart PLS. The findings revealed that brand post novelty and content quality have a significant impact on the consumer engagement while customer contact quality and brand page interactivity does not have a significant impact on  consumer engagement. Marketers and entrepreneurs may learn more about the components of how to create favourable engagement among the consumers when utilising the social media platforms. Entrepreneurs may benefit from this study as the results determine the high level of interest of consumers in content quality and brand posts novelty to stimulate engagement with businesses.
Keywords: Consumer engagement; content quality; customer contact quality; brand page interactivity; brand post novelty.